Identifying Barriers and Facilitators to Prenatal Care for Spanish-Speaking Women - Fryer, Kimberly (N C Med J, 2021)
BACKGROUND: Early access to quality prenatal care is an essential component of improving maternal and neonatal outcomes as it allows for early intervention and risk stratification. Women who receive late or infrequent prenatal care are at high risk for complications including preterm birth, infant death, and stillbirth. We sought to better understand the barriers Spanish-speaking women face in accessing quality prenatal care and to identify facilitators in obtaining timely quality prenatal care. METHODS: We recruited a homogeneous group of 11 women with Spanish as their primary language who were pregnant or had given birth within the last six months. We then conducted two focus groups in Spanish. The focus groups were recorded, translated, and transcribed, and then coded using grounded theory. RESULTS: In our cohort of participants, the three major themes included desire for psychosocial support, health care system logistics, and barriers due to Latinx ethnicity. LIMITATIONS: Our study has several limitations, including a small sample size and single site design. CONCLUSION: Latinx women experience unique barriers to care including language barriers, a lack of cultural competency on the part of health care personnel, and ethnic discrimination. Additional research is needed to develop patient-centered interventions to address these barriers.